PENGARUH PERENCANAAN PAJAK, KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN TERHADAP PRAKTIK MANAJEMEN LABA (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2018)
This study aims to determine the effect of tax planning, managerial ownership and company size on earnings management in the manufacturing companies of the automotive sub sector and components listed on the Indonesia Stock Exchange (IDX). Sampling in this study uses purposive sampling, namely the determination of samples based on certain criteria, the sample used is 4 (four) automotive sub sector manufacturing companies and components that have met the specified criteria. The results of this study indicate that partially tax planning has a positive and not significant effect on earnings management while managerial ownership and company size have a positive and significant effect on earnings management. However, simultaneous tax planning, managerial ownership and firm size have a positive and significant effect on earnings management. From the results of this study, researchers provide some suggestions for further research to get better results because the results obtained by researchers are still lacking and further research needs to be done.